Impact of Competition Versus Centralisation of Hospital Care on Process Quality: A Multilevel Analysis of Breast Cancer Surgery in France - Zeynep Or; Emeline Roccoco; Mariama Touré; Julia Bonastre (Kerman University of Medical Sciences, 2022)
BackgroundThe implications of competition among hospitals on care quality have been the subject of considerable debate. On one hand, economic theory suggests that when prices are regulated, quality will be increased in competitive markets. On the other hand, hospital mergers have been justified by the need to exploit cost advantages, and by evidence that hospital volume and care quality are related. MethodsBased on patient-level data from two years (2005 and 2012) we track changes in market competition and treatment patterns in breast cancer surgery. We focus on technology adoption as a proxy of process quality and examine the likelihood of offering two innovative surgical procedures: immediate breast reconstruction (IBR), after mastectomy and sentinel lymph node biopsy (SLNB). We use an index of competition based on a multinomial logit model of hospital choice which is not subject to endogeneity bias, and estimate its impact on the propensity to receive IBR and SLNB by means of multilevel models taking into account both observable patient and hospital characteristics. ResultsThe likelihood of receiving these procedures is significantly higher in hospitals located in more competitive markets. Yet, hospital volume remains a significant indicator of quality, therefore benefits of competition appear to be sensitive to the estimates of the impact of volume on care process. In France, the centralisation policy, with minimum activity thresholds, have contributed to improving breast cancer treatment between 2005 and 2012. ConclusionFinding the right balance between costs and benefits of market competition versus concentration of hospital care supply is complex. We find that close to monopolistic markets do not encourage innovation and quality in cancer treatment, but highly competitive markets where many hospitals have very low activity volumes are also problematic because hospital quality is positively linked to patient volume.